Dehydrated food waste and leftover for trench composting - Aziz, Khalida; Amin, Naweedullah; Nathan, Vinod Kumar; Irie, Mami; Md. Yusoff, Irwan Syah; Abdullah, Luqman Chuah; Azmi, Amirrudin; Ismail, Muhammad Heikal (Universiti Putra Malaysia Press, 2024)
The growing global population has a persistently negative impact on the economy and ecology due to food waste. This topic has recently received much attention from around the world. For both homes and the food processing industry, recycling food waste is crucial to waste management. This study aims to show how dehydrated food scraps and leftovers can be used as raw materials for trench compost to enhance soil quality and reduce leachate and greenhouse gas emissions. The results showed that the pre-treatment and air temperature significantly affected the finished trench compost products’ EC, pH, and nutrient content. Pretreated dried leftover at 80°C after trench compost was found to have the highest value of CNH, S (36.53%), and micronutrients (0.103404%) when compared to micronutrients in the final product of pre-treatment dried leftover at 80℃ after trench compost that was (0.057273%). Dehydrated leftovers from trench compost were thought to have nutrient content that would improve soil quality, slow decomposition, and reduce odor, thus enabling more frequent trash collection.